Are the final-year medical students competent enough to tackle the immunization challenges in their practice? - Jovanović Aleksa; Maričić Jovana; Marić Gorica; Pekmezović Tatjana (Vojnosanitetski Pregled)
Background/Aim. The competence of healthcare workers (HCWs) to advocate the importance of immunization to persons who are hesitant about vaccines is extremely important. The aim of this study was to evaluate the final-year medical students’ competencies related to immunization challenges in their practice using their knowledge, attitudes, and study practices. Methods. The cross-sectional study was conducted among 442 final-year students of the Faculty of Medicine, University of Belgrade, Serbia. The instrument used for data collection was an anonymous questionnaire consisting of 38 questions. Hierarchical multiple regression analysis was conducted to identify the predictive value of different factors in immunization knowledge among medical students. Results. The median total knowledge score with the interquartile range was 7 ± 3.00 out of 13. There was a statistically significant positive correlation between the knowledge score and the grade point average (GPA) (r = 0.207, p < 0.001). Thirty-five percent of students felt moderately capable of conducting work regarding vaccination without supervision. Furthermore, 92.1% of students considered that additional training and information channels about immunization needed to be implemented in curricula for HCWs. The results of the hierarchical regression analysis showed that gender, age, GPA, study duration, self-confidence regarding immunization knowledge, the flu, and hepatitis B vaccination status explained a total of 36% of the variance in the immunization knowledge score. Less than two-thirds of students believed they had enough knowledge to reassure a person hesitant about immunization. Conclusion. The results of our study showed an average level of knowledge about immunization among final-year medical students. As less than two-thirds of students believe that they have enough knowledge to reassure a hesitant person, there is a need for a better understanding and improving the parts of the curricula of medical faculties regarding immunization.